Studies of Reciprocality in Linguistics (Eurasian Scientific Herald, 2022)
The article deals with the linguistic interpretation of the concept of reciprocity. It examines the human factor, which is central to the social sciences, that reciprocity is also inextricably linked with anthropocentrism, which he finds evidence in his derivational study. Reciprocity is a logical category. This concept is expressed in the language by affixes and words. The article analyzes and comments on the views of a number of linguists